Optimalisasi Kualitas Pelayanan Jasa Menggunakan Metode Service Quality dan TRIZ - Imelda Christy Poceratu; Ivonny Y Rahanra; Jelly Lekatompessy (ARIKA, 2024)
This study aims to measure the quality of service of Health Center X towards customer satisfaction and analyze the improvement of service quality of Health Center X towards customer satisfaction based on the Servqual method and develop improvements that can be made to improve service quality using the TRIZ method. The results of the analysis showed that there were 19 negative gaps with 5 attributes that had the largest gap values, including the politeness of officers in serving patients, the attention of officers to customer needs, the accuracy of officers in checking patient conditions, officers having enough time for patient consultations, and comfortable and beautiful health center rooms. The focus of improvements to be developed by Health Center X is that officers help customers by directly handling customer requests or solving customer problems, patient examinations are carried out carefully and seriously so that mistakes do not occur, doctors provide more time and attention to patients, even the latest information about the development of the patient's condition must be conveyed directly by the doctor to the patient, even changing the layout of the benches which were initially too close together when sitting and prone to contact with others, replacing facilities that are not suitable for use or repaired and adding entertainment facilities such as TV and adding decorations such as placing plants and flowers in the room.